Development of Collaborative Learning-Based LKPD to Improve Collaboration Skills of Grade IV Elementary School Students - Setyowati, Yayuk; Nurwahidin, Muhammad; Yulianti, Dwi (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2024)
Collaboration skills are the skills of working together effectively. Ideally, students’ collaboration skills are that they are able to work together in groups, respect others, and build good relationships with their peers. the results of observations made by researchers at SDN 01 Sukamaju show that the school applies the 2013 curriculum and the teaching materials used. However, in the implementation of learning, teachers do not involve students in learning activities (teacher centered), teachers also have not used a variety of learning resources and are less than optimal in using models in learning. In learning activities, the main sources or teaching materials are textbooks and LKPD. This study aims to analyze the effectiveness and attractiveness of the development of Collaborative Learning-based student worksheets. This research is a 4-D type R & D (Research and Development) development research (define, design, develop, disseminate) in this study researchers limit it to the develop stage, the sample used amounted to 70 students. The results showed a recapitulation of the assessment of material experts, media experts and design experts getting a percentage of 92% with very feasible criteria in the development of Collaborative Learning LKPD. The effectiveness of product development received a positive response with a value of 87.3% and very high criteria. The attractiveness of the developed product shows a value of 90.5% with a very high intervention from the attractiveness of the collaborative learning LKPD implemented by researchers to students